Soft Skills as Employability Skills: Fundamental Requirement for Entry-level Jobs - Subedi, Netra Bahadur (KMC Research Journal, 2018)
In spite of the fact that the term ‘soft skills’ is new in our context, it has a wide range of implications and effects. Soft skills are intangible, nontechnical, personality-specific skills that determine one’s strengths as a leader, facilitator, mediator, and negotiator. Soft skills are contrasted to hard skills in a sense that hard skills are limited to specific area. It is to be noted that in the course of seeking an employment in the market, individual’s soft skills are as important as hard skills. It is found that person’s hard skills lead an individual to the entrance of job market, soft skills guarantee the job opportunity and further career growth. It is urgent that we have to instill our graduates with remarkable amount of soft skills for quick employment. It is always advisable that the companies select human resources with the best non-technical skills that are likely to be available in the labour market. It is further important to foster and develop the employees. Thus, these inter-sectional skills are really important for the promotion and enhancement of the organization. Owing to the same fact, this paper argues how soft skills as employability are fundamental requirement for entry-level Jobs.